Strategic Leadership Model in Regional Cooperation to Improve the Effectiveness of Resolving Drug Delivery Routes in Indonesia - Hidayatullah, Syarif; Supriyadi, Asep Adang; Purwanto, Ignatius Eko Djoko; Aritonang, Sovian; Saleh, Basuki Rahmad (Yayasan Ilomata, 2025)
This study examines the strategic leadership model in regional cooperation to enhance the effectiveness of addressing drug trafficking routes in Indonesia. Indonesia's unique geographical location makes it a crucial transit hub for drug trafficking, posing significant challenges to national security and regional stability. Despite numerous efforts to combat drug trafficking, the lack of coordinated regional leadership remains a persistent barrier. This research specifically addresses the question: How can a strategic leadership model improve regional cooperation effectiveness in resolving drug trafficking in Indonesia?. The novelty of this paper lies in its comprehensive analysis of the strategic leadership model's application specifically within the ASEAN regional cooperation framework, which has not been extensively studied previously. Unlike other studies, this research identifies specific institutional, technological, and political barriers and offers a structured framework to address accountability and cross-border legal harmonization. This paper employs a descriptive qualitative approach and literature review, analyzing data sourced from internationally indexed academic journals, institutional reports, and publications from international bodies such as ASEAN and the UNODC. A thematic analysis approach, complemented by source triangulation, is utilized to ensure data validity and reliability.: The findings indicate that effective regional strategic leadership significantly reduces drug trafficking activities through improved coordination, harmonized law enforcement, advanced technology integration, and structured anti-corruption measures. Comparative case studies from Thailand’s Golden Triangle Operation and drug enforcement strategies in Mexico underline the critical role of cohesive strategic leadership. The study concludes that implementing a structured strategic leadership framework is essential to overcoming existing political and institutional barriers, enhancing regional cooperation effectiveness. Policymakers in ASEAN nations, particularly Indonesia, should prioritize establishing transparent accountability mechanisms, harmonizing cross-border laws, strengthening anti-corruption efforts, and promoting high-level diplomatic engagements to effectively combat drug trafficking